3D Nanoscale Morphology Characterization of Ternary Organic Solar Cells. Issue 1 (7th December 2021) - Yu, Ting; He, Wanting; Jafari, Maziar; Guner, Tugrul; Li, Pandeng; Siaj, Mohamed; Izquierdo, Ricardo; Sun, Baoquan; Welch, Gregory C.; Yurtsever, Aycan; Ma, Dongling
Abstract: It is highly desired to develop advanced characterization techniques to explore the 3D nanoscale morphology of the complicated blend film of ternary organic solar cells (OSCs). Here, ternary OSCs are constructed by incorporating the nonfullerene acceptor perylenediimide (PDI)‐diketopyrrolopyrrole (DPP)‐PDI and their morphology is characterized in depth to understand the performance variation. In particular, photoinduced force microscopy (PiFM) coupled with infrared laser spectroscopy is conducted to qualitatively study the distribution of donor and acceptors in the blend film by chemical identification and to quantitatively probe the segmentation of domains and the domain size distribution after PDI‐DPP‐PDI acceptor incorporation by PiFM imaging and data processing. In addition, the energy‐filtered transmission electron microscopy with energy loss spectra is utilized to visualize the nanoscale morphology of ultrathin cross‐sections in the configuration of the real ternary device for the first time in the field of photovoltaics. These measurements allow to "view" the surface and cross‐sectional morphology and provide strong evidence that the PDI‐DPP‐PDI acceptor can suppress the aggregation of the fullerene molecules and generate the homogenous morphology with a higher‐level of the molecularly mixed phase, which can prevent the charge recombination and stabilize the morphology of photoactive layer. Abstract : Ternary organic solar cells are fabricated by rationally selecting and incorporating the perylenediimide (PDI)‐based nonfullerene acceptor, PDI‐diketopyrrolopyrrole‐PDI, as the third component into a model solar cell and their 3D morphology is qualitatively and quantitatively explored at the nanoscale by developing the new use of advanced characterization tools in the field of photovoltaics.